Isolation and Diagnosis of Microorganism from Sandwiches (Street-Food and Fast Food): Isolasi dan Diagnosis Mikroorganisme dari Sandwich (Makanan Jajanan dan Makanan Cepat Saji) - Ali Y. Khudhair; Saif al deen M. Khatlan; Suaad W. Kadium (Universitas Muhammadiyah Sidoarjo, 2025)
Fifty food samples were collected from 60 randomly chosen fast food and traditional restaurants in Al-Najaf, Iraq. These samples were incubated to encourage bacterial growth at 37°C for 24 to 48 hours, while fungi were cultured at 25°C for seven days. The analysis showed that out of the 17 samples isolated from the food, nine different bacterial genera and ten fungal genera were identified, the bacterial and fungal species isolated in this study included Staphylococcus aureus, Shigella sp., Escherichia coli, Streptococcus sp., Salmonella sp., Bacillus subtilis, Aspergillus fumigatus, Aspergillus flavus, Aspergillus niger, Aspergillus terreus, Penicillium expansum, Penicillium sp., Rhizopus sp., Cladosporium sp., Alternaria sp., and Fusarium sp. The findings revealed that Aspergillus niger was the most predominant species, followed by Penicillium sp., and then Aspergillus flavus and Alternaria sp., with their respective frequencies being 52%, 45%, 50%, and 31.3%. The occurrence rates in falafel were 80%, 75%, 73%, and 45% respectively. In the case of beef burgers, Aspergillus flavus was predominant, with a frequency and visible percentage of 36%, 53%, and 35% respectively. Cladosporium sp. showed the lowest frequency and appearance percentage in beef pizza, with values of 26% and 6.6% respectively. Highlights: Food samples tested: 9 bacterial, 10 fungal species identified. Aspergillus niger predominant in falafel, beef burgers, and beef pizza. Cladosporium sp. showed lowest frequency and appearance in beef pizza. Keywords: Street-Food , Fast Food, Staphylococcus aureus, Sandwiches